I am Neil Armstrong - Meltzer, Brad.; Eliopoulos, Chris (New York, NY : Dial Books for Young Readers, 2018)
"A biography of Neil Armstrong, the first man to walk on the moon"-- Provided by publisher.
Includes bibliographical references.
3.0
K-3.
K-3
Keywords: Armstrong, Neil, -- 1930-2012 -- Juvenile literature; Armstrong, Neil, -- 1930-2012.; Armstrong, Neil, -- 1930-2012.; Astronauts -- United States -- Biography -- Juvenile literature; Astronauts; Astronauts -- United States -- Biography; Biographies; Picture books